Interreligious Dialogue in Secondary Education : Building Foundations for Peace - Griet Galle; Paul Smeyers; Marc Depaepe (Green Philosophy: International Journal of Religious Education and Philosophy, 2024)
Interreligious dialogue is a vital component of religious education, especially in regions marked by cultural and religious diversity. This paper examines the role of interfaith initiatives in secondary education, highlighting their impact on reducing prejudice and fostering peace. Case studies from schools in diverse contexts illustrate how dialoguebased curricula can create a more inclusive and harmonious learning environment. The study concludes with recommendations for policymakers and educators.